Exploring the Philosophical and Historical Values of Sotong Pangkong as a Malay Culinary Cultural Heritage - Emi Tipuk Lestari; Saiful Bahri; Arif Teguh Susanto; Agi Rohadi (Journal of Education Technology Information Social Sciences and Health, 2026)
Sotong Pangkong is a traditional Malay culinary heritage that reflects local wisdom, cultural identity, and philosophical and historical values ​​passed down through generations, yet it has not received much academic study. This study aims to explore the philosophical values, historical development, and cultural significance of Sotong Pangkong as a Malay culinary heritage. The study used a qualitative approach with an ethnographic design. Data were obtained through participant observation, in-depth interviews with traditional food vendors, cultural practitioners, community leaders, and local historians, as well as analysis of historical documents and related literature. Data analysis was conducted using thematic analysis through data reduction, categorization, interpretation, and triangulation to ensure the credibility of the findings. The results show that Sotong Pangkong functions not only as a traditional food but also as a cultural symbol that represents the values ​​of togetherness, simplicity, gratitude, and harmony of the Malay community with the coastal environment. Historically, this culinary tradition evolved from the fishing community's tradition of preserving seafood to become a cultural identity and culinary tourism attraction. Furthermore, Sotong Pangkong plays a role in maintaining collective memory, strengthening social cohesion, and supporting the preservation of intangible cultural heritage amidst the challenges of modernization. These findings contribute to the development of gastronomic studies, cultural education, and policies for the preservation of traditional Indonesian cuisine.